Does socioeconomic status account for racial and ethnic disparities in childhood cancer survival? - Kehm, Rebecca D (Cancer, 2018)
BACKGROUND: For many childhood cancers, survival is lower in non-Hispanic blacks and Hispanics compared to non-Hispanic whites, which may be attributed to underlying socioeconomic factors. However, prior childhood cancer survival studies have not formally tested for mediation by socioeconomic status (SES). We applied mediation methods to quantify the role of SES in racial/ethnic differences in childhood cancer survival. METHODS: We used population-based cancer survival data from the Surveillance, Epidemiology, and End Results 18 database for black, white, and Hispanic children, ages 0-19 years, diagnosed 2000-2011 (N=31,866). We estimated black-white and Hispanic-white mortality hazard ratios (HR) and 95% confidence intervals (CI), adjusted for age, sex, and stage at diagnosis. We used the inverse odds weighting (IOW) method to test for mediation by SES, measured with a validated census tract composite index. RESULTS: Whites had a significant survival advantage over blacks and Hispanics for several childhood cancers. SES significantly mediated the race/ethnicity-survival association for acute lymphoblastic leukemia, acute myeloid leukemia, neuroblastoma, and non-Hodgkin lymphoma; SES reduced the original association between race/ethnicity and survival by 44% ((log hazard ratio total effect – log hazard ratio direct effect)/log hazard ratio total effect), 28%, 49%, and 34% respectively for blacks vs. whites, and by 31%, 73%, 48%, and 28% respectively for Hispanics vs. whites. CONCLUSIONS: SES significantly mediates racial/ethnic childhood cancer survival disparities for several cancers. However, the proportion of the total race/ethnicity-survival association explained by SES varied between black-white and Hispanic-white comparisons for some cancers, suggesting that mediation by other factors differs across groups.